Musical Iconography and its Didactic: between mimesis and symbol in the context of teacher training - Susana Alicia Sarfson Gleizer (Universitat Politècnica de València, 2015)
This   paper   reflects   on   the   possibilities that  musical  iconography  offers  as  the starting   point   for   a   complex   learning integrating  both  visual  and  musical  art experiences  following  a  humanistic  and comprehensive approach, in the context of university teacher training. Firstly, it refers to   the   theoretical   and   epistemological framework  related  both  to  the  specific teaching  involved  and  to  art  history  and the  rhetoric  of  the  image  that  has  been considered.  Then  an  experience  of  action research   is   presented,   conducted   with university    teacher    trainees    (belonging to  Initial  and  Primary  levels),  based  on musical  iconography  and  its  teaching,  so as  to  integrate  competencies  through  the artistic  experience.  We  sought  to  provide learning  situations  that  would  promote not  only  reflection,  but  also  a  knowledge of  a  repertoire  of  music  and  of  visual  art works  and  some  of  the  symbols  that  may be present in them, and also to bring about direct   artistic   experiences   through   the reprocessing  of  these  works  using  various techniques.